Glossary of Geology - Swedish Centre for Terminology TNC (Institute for Language and Folklore, 2023)
Multilingual terminology glossary containing terms from the geological field. The glossary contains 1745 terms in Swedish, some of the terms have been translated to Russian, Spanish, German, Finnish, Norwegian, Danish, French and English.

Flerspråkig terminologisamling som rör geologiska termer. Samlingen innehåller 1745 termer på svenska. Somliga termer är översatta till ryska, spanska, tyska, finska, norska, danska, franska, och engelska
Geologisk ordlista
Keywords: geosciences; geovetenskaper; geology; geologi; multilingualism; flerspråkighet; terminology; terminologi; Term glossary; Termlista; Languages and Literature; Språk och litteratur